Tiapride for the Treatment of Auditory Hallucinations in Schizophrenia - Karia, Sagar (Medknow Publications & Media Pvt Ltd, 2013)
Hallucinations are considered as core symptoms of psychosis by both International Classification of Diseases–10 (ICD-10) and Diagnostic and Statistical Manual for the Classification of Psychiatric Disorders – 4(th) edition text revised (DSM-IV TR). The most common types of hallucinations in patients with schizophrenia are auditory in nature followed by visual hallucinations. Few patients with schizophrenia have persisting auditory hallucinations despite all other features of schizophrenia having being improved. Here, we report two cases where tiapride was useful as an add-on drug for treating persistent auditory hallucinations.